Dynamic Behaviour and Catenary Action of Axially-restrained Steel Beam Under Impact Loading. (August 2017) - Huo, Jingsi; Zhang, Jinqing; Liu, Yanzhi; Fu, Feng
Abstract: In this paper, the dynamic response and catenary action of axially restrained steel beam under impact loadings is examined through a combination of experimental and numerical investigations. The results of six impact tests on the axially restrained welded H-beams by means of the drop hammer test machine are presented. The main behavioural patterns and the key response characteristics including the development of impact force, deformation and strain, as well as failure modes are examined, with emphasis on the effect of impact energy and the width to thickness ratio of beam flange. Finite element models are also developed and validated against the available testing results. It is demonstrated that the detailed FE model can reasonably capture the response of the welded H-beams under impact loadings. Moreover, the mechanism of catenary action was identified based on the development of the internal force in the welded H-beams.